Impact of Religion-Based Caste System on the Dynamics of Indian Trade Unions: Evidence From Two State-Owned Organizations in North India. Issue 5 (May 2020) - Pandey, Jatin; Varkkey, Biju
Religion and its envisaged structures have both macro- and micro-level implications for business. Of the many stratification schemas prevalent in India, two macro-social stratification schemas are important at the workplace: caste, which has been an age-old, religion-mandated, closed social stratification prevalent in Hinduism that had led to inequality in the society, and trade union, which is a relatively new and optional open workplace stratification that empowers workers and fosters equality. This study tries to decipher whether these two structures influence each other; if yes how and why do they influence each other (the tensions and contradictions that may happen between them), and whether the influence is uniform for all members. We conducted in-depth interviews with 43 trade union members, three trade union leaders of two state-owned organizations in North India. Initially, we found that caste does not have any superficial effect on the relationship between union members. However, a deeper analysis reveals that roots of this social reality reflect in the social and workplace exchanges between union members, and affect their social identity and loyalty. In the discussion we present a model of twin loyalties between union and caste. From the institutional logic perspective, we also delineate the caste and trade union perspective, and show how there is a change in trade union identity because of the influence of caste-based logic. Our findings have implications for industrial democracy, worker representation, and union effectiveness.